2009
DOI: 10.1103/physreva.80.033844
|View full text |Cite
|
Sign up to set email alerts
|

Photon-pair generation in random nonlinear layered structures

Abstract: Nonlinearity and sharp transmission spectra of random 1D nonlinear layered structures are combined together to produce photon pairs with extremely narrow spectral bandwidths. Indistinguishable photons in a pair are nearly unentangled. Also two-photon states with coincident frequencies can be conveniently generated in these structures if photon pairs generated into a certain range of emission angles are superposed. If two photons are emitted into two different resonant peaks, the ratio of their spectral bandwid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…We note that there also exist photon pairs emitted at the boundaries [27,28,32] that are not described by Eq. (8).…”
Section: Model Of Spontaneous Parametric Down-conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that there also exist photon pairs emitted at the boundaries [27,28,32] that are not described by Eq. (8).…”
Section: Model Of Spontaneous Parametric Down-conversionmentioning
confidence: 99%
“…These structures have been shown to be able to provide entangled photon pairs anti-symmetric with respect to the exchange of signal and idler frequencies [24]. Also random nonlinear dielectric layered structures have been analyzed as sources of spectrally ultra-narrow photon pairs [25,26]. Surface SPDC has been shown to give important contribution to photon-pair generation rates [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…(4) and (9) and characterize the fields outside the structure. We note that the approach based on the solution of Schrödinger equation does not take into account surface SPDC that generates additional photon pairs [48,49].…”
Section: Spatial Quantum Model Of Spontaneous Parametric Down-conmentioning
confidence: 99%
“…This allows us to study transverse intensity profiles of the down-converted beams as well as correlated areas of the signal and idler photons considering typical layered structures made of GaN/AlN. We note that GaN/AlN structures with random layers' lengths have already been studied as sources of photon pairs with ultra-narrow spectral widths that originated in an optical analog of Anderson localization of the down-converted fields [44,45]. It has also been shown that GaN/AlN nonlinear layers allow the generation of photon-pair states antisymmetric with respect to the exchange of the signal-and idler-field frequencies that exhibit anti-bunching and anti-coalescence [46].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of introducing static disorder in a quantum random walk (leading to Anderson localization) have been studied, for example, for one-dimensional [16][17][18] and two-dimensional [19] systems. In a sense, generalizations of quantum protocols such as the Shor's factorization algorithm [20] and the Groover's searching algorithm [21] can also be analyzed in similar terms, since they can be viewed as quantum random walks.…”
Section: Introductionmentioning
confidence: 99%